Determinan Kemampuan Auditor Dalam Mendeteksi Kecurangan - Siti Samsiah; Agustiawan Agustiawan; Ainun Jariah (Akuntansi & Ekonomika, 2022)
Stakeholders in decision-making really need reliable and valid financial reports. Financial statements are reliable if they have passed an examination process called an audit. The audit of financial statements is carried out to provide an explanation that the financial statements are free from material misstatement and avoid harmful actions or fraud. This study was conducted to analyze the determinants of the auditor's ability to detect fraud. Respondents selected in this study were auditors who worked at KAP in Pekanbaru as many as 45 respondents. Furthermore, data processing is carried out based on the results of distributing questionnaires to 45 respondents with the help of statistical tools in the form of SPSS V 25. The processed data results prove that the determinants of workload, audit experience, personality type and self efficacy have a significant influence on the auditor's ability to detect fraud.